Straatname as monumentale nalatenskap van akademici aan die Universiteit van die Oranje-Vrystaat (UOVS): Die geval van die padnetwerk in Universitas, Bloemfontein - Burgert A. Senekal (Contree, 2016)
Street names represent a monument in the everyday world that commemorates the contributions of people in a particular community, and often of a particular era. The present study investigates how street names in the neighbourhood (suburb) Universitas in Bloemfontein serve as monuments to the contributions of academics at the University of the Orange Free State (UOFS), as well as its predecessors, the Grey University College (GUC) and University College of the Orange Free State (UCOFS) – currently the University of the Free State or UFS. The main streets in this neighbourhood are identified using network theory, and it is indicated that it is especially academics belonging to the two oldest faculties at this university, namely Natural Sciences and the Humanities, after which key streets are named. In addition, it is indicated that, to a large extent, the importance of streets also reflects the UFS’s past Afrikaans character as the main streets are named after academics who worked for the Department of Afrikaans and Dutch (for example DF Malherbe and H van der Merwe Scholtz), but also other leaders, such as Wynand Mouton’s outstanding contributions to the establishment of the UFS as a research university, are commemorated.